High-density lipoprotein subfractions - What the clinicians need to know - Pirillo, A.; Norata, Giuseppe; Catapano, A. (2013)
Copyright © 2013 S. Karger AG, Basel. Although the inverse relationship between plasma levels of high-density lipoprotein (HDL) and cardiovascular disease has been largely demonstrated, many observations have suggested that the assessment of HDL functionality might be more informative than a simple measurement of HDL-cholesterol plasma levels. HDLs are a class of structurally and functionally heterogeneous particles; in atherosclerosis-related diseases, changes in HDL subfraction levels and functions are frequently observed. Circulating levels of large HDL particles are decreased in dyslipidaemic conditions, while levels of small dense HDL particles are increased in patients with coronary heart disease. Furthermore, specific genetic defects in proteins involved in HDL metabolism significantly impact the distribution of HDL subpopulations. Finally, many drugs used for dyslipidaemia induce changes in HDL subfractions strictly related to cardiovascular disease. Although several methods exist to evaluate HDL subclass levels, most of them are not easily applicable in clinical practice, due to the costs and high variability. However, the possibility to measure the levels of specific HDL subfractions in patients with atherosclerosis-related diseases might help to better define their cardiovascular risk.